Credibility talk in public diplomacy - Mor, Ben D. (2012)
Employes rhetorical theory, impression management theory, and account theory to situate contests of credibility within the broader context of accountability of social conduct. Discusses the rhetorical strategies that actors use to credit their accounts and discredit those of their rivals.